Produção textual na tela : contribuições do letramento digital na EJA em uma escola pública de Gravatá - PE - Freire, Jamyle Sabino (2014)
This research aims to investigate the contributions of digital literacy for the development of the production of texts in Portuguese Language in Education for Youths and Adults (hereinafter EJA) - Level III (corresponding to 6 and 7 years of elementary school) - in a public school in the municipality of Gravatá-PE. This is a qualitative- quantitative research, because it is the analysis of skills to produce texts in a different space - on the screen, from the conception of gender perspective in Bakhtin. To achieve this end, we apply initially questionnaires to identify the class of EJA III "D" Night of MS in order to know the profile of the subjects participating in research related to digital media. Im 38 subjects in the aforementioned class, which we applied the questionnaire, we selected five subjects (S9, S15, S20, S34 and S35) which effectively made all proposed activities in the digital environment, from the discursive genre e-mail to analysis of the corpus of research on screen. We believe that this adequately met the full requirements for the type of research we set out to accomplish: a case study. Then, specifically, we observed the production of discourse genre e-mail (form, style, content and function), the digital environment, in order to analyze the productions of the subjects before and after the practices of digital literacy promoted in Portuguese Language classes. That´s why, we conducted six weekly lessons in the period from April to August of 2013. After analysis, we found that the five subjects showed improvements in planning the text and began to structure it properly - in line with the organizational format of the genus email to be produced. Thus, we believe that the practices of digital literacy promoted advances in the production of texts in this particular group of students from the EJA.